Itti'at akka' wáyya'ahookya ikkobaffo (Trees bend, but don’t break): Chickasaw family stories of historical trauma and resilience across the generations - Aducci, Christopher John (Kansas State University, 2013)
The Chickasaw represent one non-reservation bound American Indian tribe whose experiences of family life, historical trauma and resilience has not been fully understood. Therefore, this study sought to identify the qualities common to Chickasaw families, Chickasaw families' experiences of historical trauma and the factors that contribute to Chickasaw families' ability to persevere under adversarial circumstances. Using in-depth phenomenological interviews with nine (N = 9) three-generation minimum Chickasaw families, four central themes emerged that answered the four research questions. The first theme, "Chokka-chaffa' Nanna Mó̲́đma Ímmayya/The Family Is Everything" indicated that Chickasaw families were a heterogeneously complex system with a natural orientation toward the family unit itself, whereby the families valued emotional closeness, warmth and affection, quality time together, praise, respect and openness. Families were involved with one another and were active participants in strengthening their own families and communities. Families were prideful of family members' accomplishments and valued extended kin and spirituality. Further, families were confronted with challenges, but showed an ability to "bend, but not break," often citing the very same qualities, such as involvement, pride and an orientation toward family, as contributing to their ability to solve problems and keep the family unit intact. The second theme, "Impalahá̲mmi Bíyyi'ka/They Have It Really Bad," indicated the families experienced historical trauma by mourning the loss of land, language, culture and identity and that losses went unacknowledged by their non-Native counterparts and were ongoing, thus expecting to affect younger and future generations. The third theme, "Chikashsha Poyacha Ilaa-áyya'shakatí̲'ma/We Are Chickasaw, and We Are Still Here" indicated that despite hardships, families saw resilience as a trait found within their Chickasaw heritage. Maintaining a positive outlook, a spirit of determination, a fierce loyalty toward family members and a close connection to the Chickasaw Nation further contributed to families' resilience. The fourth theme, "Hooittapila/They Help One Another" indicated that resilient qualities were passed in a multidirectional pattern throughout all generations of family members, whereby family members from all generations supported and uplifted one another. Also discussed are the study's strengths and limitations and the clinical and research implications for Chickasaw families.
Keywords: Chickasaw; American Indian; Historical trauma; Resilience; Couple and family therapy; Phenomenology; Individual & Family Studies (0628)